Ferramenta de auxílio ao desenvolvimento do pensamento computacional: uma plataforma robótica controlada por smartphone - Reis, Cibele Alves da Silva (2014)
The dificulty of students in learning logic and programming languages leads to the creation of many technological solutions to assist in the teaching-learning process. Among these solution, two common approaches are robotics and graphical programming based languages. Researches indicate that these tools can help youth to think systematically and develop computational thinking, and that this result can be enhanced with the application of a problem based learning methodology. Therefore, this work describes the development of Plataforma Coffee, which involves a block programming Web environment and a smartphone as a robot controller unit. This platform can be easily expanded to work with various mobile devices and robotic kits. Another accomplishment of this work was the application of the platform in a classroom with the aim of evaluating the tool produced and the students' motivation while using it. Besides the tool evaluation by student, it was performed a heuristic usability evaluation of the Web programming environment, in which was verified that the platform is aesthetically pleasing and consistent in its content. At the end of this work, it was possible to observe that the presented solution can serve as a stimulus for students and assist in understanding programming concepts.